Towards Autocephaly: Challenges Faced by the Latvian Orthodox Church - Jefuni, Juris (Religion and society in Central and Eastern Europe, 2025)
Following the Russian invasion of Ukraine, publicly supported by Patriarch Kirill of Moscow, the issue of the Latvian Orthodox Church's subordination to the Russian Orthodox Church gained significant relevance. Although Orthodox believers in Latvia embarked on their journey towards autocephaly prior to World War II, they were ultimately unable to achieve this status completely for a variety of reasons. Drawing on historical sources, this article explains the Latvian Orthodox Church's pursuit of autocephaly before the World War II and how this pursuit affects the Latvian Orthodox Church's status today. The article sheds light on the rationale behind the amendments to the law adopted by the Parliament of the Republic of Latvia, highlighting that the Latvian Orthodox Church is completely independent and free from the power of any church outside Latvia.